Selametam Tradition of Wedding Ceremony in Mandungan Hamlet, Bringin Village, Srumbung Subdistrict, Magelang Regency - Annisa Rahmawati (Pusat Studi Penelitian dan Evaluasi Pembelajaran, 2023)
Every region in Indonesia must have a tradition that is carried out before or after the wedding procession. Many things are behind the differences in traditions in each region, for example, customs that have existed since long ago in each region. One of the traditions that exist in Java, especially in the Magelang Regency area before or before the wedding is selamatan. Selamatan or usually called selametan is a tradition carried out before the wedding day. This tradition has been around for a long time and has become a hereditary custom of the Javanese community, especially in the Magelang Regency area, Central Java. The purpose of writing this scientific essay is to explore and examine the nature of selametan in marriage based on factual events held in Mandungan Hamlet, Bringin Village, Srumbung Subdistrict, Magelang Regency and see the phenomenon based on Urf review. The research method used is fieldwork, observation, and interviews, with a normative juridical approach with Urf theory. The results of this study indicate that the marriage tradition in Bringin Village is very close in upholding the Javanese tradition and culture in the marriage procession, one of the series of ceremonies is the selametan tradition, this is in line with the theory of al-adah muhakkamah which has been going on for dark ancestors.